Effect of physical exercise combined with shockwave therapy on erectile dysfunction in diabetic patients - Amr B. Salama; Mohamed Samy Abdrabo; Walid A. Abouelnaga (Archives of Medical Science, 2021)
Introduction The aim of the study was to evaluate whether physical exercise (PE) in addition to extracorporeal shockwave therapy (ESWT) is more effective in improving erectile function as compared to ESWT and PE alone in diabetic patients with erectile dysfunction (ED).